Bildgebende Diagnostik des Innenohrs vor Cochleaimplantation - Mack, Martin G.; Suckfüll, Markus M. (Laryngo-Rhino-Otologie, 2020)
If sufficient speech understanding can no longer be achieved with conventional hearing aids, the indication for a cochlear implant is very often present. Imaging plays an important preoperative role, as it is the only way to decide whether a cochlear implant is possible or not. The preoperative evaluation of the temporal bone for the precise selection of the candidates for cochlear implant is including CT (Computed Tomography) and MRI (Magnetic Resonance Imaging).
Keywords: Cochleaimplantat; Bildgebung; Mittelohrfehlbildung; Länge der Cochlea; Innenohrfehlbildung